If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 13y + 5 = 0 Reorder the terms: 5 + 5x + 13y = 0 Solving 5 + 5x + 13y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + 5x + -5 + 13y = 0 + -5 Reorder the terms: 5 + -5 + 5x + 13y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 5x + 13y = 0 + -5 5x + 13y = 0 + -5 Combine like terms: 0 + -5 = -5 5x + 13y = -5 Add '-13y' to each side of the equation. 5x + 13y + -13y = -5 + -13y Combine like terms: 13y + -13y = 0 5x + 0 = -5 + -13y 5x = -5 + -13y Divide each side by '5'. x = -1 + -2.6y Simplifying x = -1 + -2.6y
| -11-(-15)= | | -3(4r-80)=-36 | | 180=4/(x-4) | | y=2(x-7) | | w-(4/2/5)=(9/3/5) | | 11-x=19 | | 13+w/7 | | (m-3)=5 | | 7y+14=-15y+10+6y | | 16x+42-13x=20+4 | | 10a+a-7a= | | X/3+3=x/2+2 | | 2=(n+1) | | 2(p+3)=8 | | 6x+37=14x-32 | | 4x-5+2x=7x-1 | | -n+23=-2(1-4n)-2 | | y=100-12x^3 | | 2s+4t=8 | | 3x+4/3=2x-1 | | 3(2x-5)+16=x-9 | | 6-(a+2)=9 | | -8-3x=2x+13 | | C=8/7(k-26) | | 2x+4=2(4x-3)-3(-8+4x) | | 0.2(x-2)+0.5(x+5)=0 | | x^2/3x-5=0 | | 7(2x-4)=8 | | 5b+7=-23 | | X+45=-5y | | 8+12x=52x+x | | 3+6y=13+6z |